2018
DOI: 10.3354/aei00255
|View full text |Cite
|
Sign up to set email alerts
|

Adding value to ragworms (Hediste diversicolor) through the bioremediation of a super-intensive marine fish farm

Abstract: The aim of this study was to evaluate the potential added value of Hediste diversicolor, cultured for 5 mo in sand bed tanks supplied with effluent water from a super-intensive marine fish farm, by comparing their fatty acid (FA) profile with that of wild specimens. The polychaetes showed an approximately 35-fold increase in biomass during the experimental period and their FA profile was significantly different from that of wild specimens. In cultivated specimens, the most abundant FA class was that of highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 31 publications
1
36
1
Order By: Relevance
“…A recent study confirmed the potential of this species for the bioremediation of intensive marine fish farm effluents and highlighted its ability to retain high-value nutrients (e.g. HUFA in general and EPA in particular, and to a lesser extent DHA) from fish feeds that would otherwise be lost from the production environment (Marques et al 2018). Fowler (1999) should be taken into consideration.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…A recent study confirmed the potential of this species for the bioremediation of intensive marine fish farm effluents and highlighted its ability to retain high-value nutrients (e.g. HUFA in general and EPA in particular, and to a lesser extent DHA) from fish feeds that would otherwise be lost from the production environment (Marques et al 2018). Fowler (1999) should be taken into consideration.…”
Section: Introductionmentioning
confidence: 80%
“…HUFA in general and EPA in particular, and to a lesser extent DHA) from fish feeds that would otherwise be lost from the production environment (Marques et al . ).…”
Section: Polychaete's Potential For Aquaculturementioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, they can incorporate the valuable nutraceutical compounds from wasted aquafeeds, such as EPA and DHA fatty acids, adding value to the production (Marques et al . ).…”
Section: Aquaculture Can Deliver Key Ecosystem Servicesmentioning
confidence: 97%